1998
DOI: 10.1073/pnas.95.11.6413
|View full text |Cite
|
Sign up to set email alerts
|

t(11;22)(q23;q11.2) in acute myeloid leukemia of infant twins fuses MLL with hCDC rel , a cell division cycle gene in the genomic region of deletion in DiGeorge and velocardiofacial syndromes

Abstract: Medical Sciences. In the article "t(11;22)(q23;q11.2) in acute myeloid leukemia of infant twins fuses MLL with hCDCrel, a cell division cycle gene in the genomic region of deletion in DiGeorge and velocardiofacial syndromes" by Maureen D. Megonigal, Eric F. Rappaport, Douglas H. Jones, Terrence M. Williams, Brian D. Lovett, Kara M. Kelly, Paul H. Lerou, Thomas Moulton, Marcia L. Budarf, and Carolyn A. Felix, which appeared in number 11, May 26, 1998, of Proc. Natl. Acad. Sci. USA (95, pp. 6413-6418), the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
123
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 35 publications
5
123
1
1
Order By: Relevance
“…MLL translocations in infant leukaemias are in utero events (Ford et al, 1993;Gale et al, 1997;Gill-Super et al, 1994;Mahmoud et al, 1995;Megonigal et al, 1998). MLL has many partner genes that encode proteins of several different types (reviewed in Ayton and Cleary, 2001;Felix, 2000;Rowley, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…MLL translocations in infant leukaemias are in utero events (Ford et al, 1993;Gale et al, 1997;Gill-Super et al, 1994;Mahmoud et al, 1995;Megonigal et al, 1998). MLL has many partner genes that encode proteins of several different types (reviewed in Ayton and Cleary, 2001;Felix, 2000;Rowley, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…2 At least 14 partner genes (on chromosomes 1, 4, 6, 9, 10, 16, 17, 19, 22 and X) have been fully characterized. [3][4][5][6][7][8][9][10][11][12][13][14][15] The role of these partner genes in leukemogenesis and the possible prognostic impact of distinct 11q23 translocations is largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…This gene maps to the central portion of a 1.3-megabase sequence that is part of the region commonly deleted in patients with del22q11.2. On investigation of two infant twins with acute myeloid leukemia, the authors demonstrated fusion of the MLL gene this resulted in the chromosomal anomaly t(11;22)(q23;q11.2) and also caused acute myeloid leukemia [14]. The above-mentioned reports suggest that the 22q11 region includes gene(s) that may be involved in the pathogenesis of MD and certain malignancies.…”
Section: Discussionmentioning
confidence: 97%
“…Two other reports described a 7-month-old boy and a 10-month-old girl with DGS who developed B-cell lymphoma and B-cell non-Hodgkin's lymphoma, respectively [12,13]. In addition to these accounts, a recent study described a role for the human cell division cyclerelated (hCDCrel) gene in malignant conditions [14]. This gene maps to the central portion of a 1.3-megabase sequence that is part of the region commonly deleted in patients with del22q11.2.…”
Section: Discussionmentioning
confidence: 99%